Differential changes of fat-soluble vitamins and pollutants during lactation in northern elephant seal mother-pup pairs. - Debier, Cathy; Crocker, Daniel E.; Houser, Dorian S.; Vanden Berghe, Marie; Fowler, Melinda; Mignolet, Eric; de Tillesse, Tanguy; Rees, Jean-FranÃ§ois; ThomÃ©, Jean-Pierre; Larondelle, Yvan (Comparative Biochemistry and Physiology Part A: Molecular & Integrative Physiology, 2012)
We investigated the changes of vitamins A and E as well as PCBs and DDTs during lactation in northern elephant seal (Mirounga angustirostris) mother-pup pairs. On average, milk vitamin A concentrations were 6 times higher during late lactation than during early lactation, a pattern that differs dramatically from terrestrial mammals. Vitamin A concentrations also significantly increased in the inner blubber throughout lactation, whereas they remained constant in the outer blubber. Similar dynamics were observed for PCBs and DDTs in maternal blubber and milk. Blubber appears to be an important storage site for vitamin A and organochlorines in seals and a direct transfer of those molecules to the mammary gland may occur. The dynamics of vitamin A, PCBs and DDTs differed from those of vitamin E. There was a significant drop in milk vitamin E concentrations between early and late lactation, which is the usual pattern observed in terrestrial mammals. The dynamics of vitamin E in the blubber layers also differed from those of vitamin A, suggesting different mechanisms of mobilization and transfer into the milk.